Collaborative Learning Techniques A Handbook for college Faculty ; Second Edition - Barkley, Elizabeth F; Cross, K. Patricia; Major, Claire Howell (San Francisco, USA A Wiley Brand, 2014)
The book reflects the changed world of higher education and offers college and university faculty a definitive guide for making the most of small group learnning. in this new edition, the authors include ideas for using games in technologically-sophisticated curricula, information on effective online implementation for each of the book's thirty-five techniques in a variety of learning environments, including large lecture class and "flipped" classes. The authors guide instructors through all aspects of group work and provide a solid grounding in what to do, how to do it, and why it is important for student learning
Contents : Establishing The Context -- Implementing Collaborative Learning -- Collaborative Learnnig Techniques
"Include Index"
12
NEW_ZAG_GN
Keywords: Collaborative Learning; Educational games; Learning techniques